EATING DISORDERS IN PATIENTS WITH CHRONIC GASTRITIS AND TYPE 2 DIABETES MELLITUS - D. D. Kazarin; A. E. Shklyaev; Yu. V. Gorbunov (SINAPS LLC, 2019)
Diabetes mellitus holds one of the leading positions among the current problems of modern medicine. Despite the obvious success in studying diabetes in the last decades, its prevalence has become pandemic. In spite of the use of modern methods of therapy, a rather high frequency of diabetes mellitus complications from various organs and systems, the pathological changes in which largely determine the course of the disease and patient's quality of life remains. Issues of eating disorders and their correction play an important role in the complex therapy of patients with diabetes mellitus. Objective: determination of the characteristics and relationship of eating disorders with gastroenterological symptoms and glucose levels in patients with chronic gastritis in type 2 diabetes. Materials and methods: dynamic study of the eating behavior and quality of life in 66 patients with chronic gastritis in type 2 diabetes mellitus was conducted using GSRS, SF-36 and DEBQ questionnaires. The level of glucose on an empty stomach and after eating was also measured, the frequency of self-measurement of glucose level and the presence of diabetes mellitus complications were determined. Results: the identified correlation relationships suggest that gastrointestinal symptoms characteristic of chronic gastritis with type 2 diabetes mellitus worsen the physical and psychological components of health, which provokes a breakdown and a violation of the diet in this category of patients. Conclusion: chronic gastritis in patients with type 2 diabetes mellitus aggravates the prognosis of diabetes and exacerbates eating disorders, which requires observation of an endocrinologist, as well as a gastroenterologist and psychotherapist in the management of such patients.